Methodologies to unlock the molecular expression and cellular structure of ocular lens epithelial cells - Parreno, Justin; Emin, Grace; Vu, Michael P.; Clark, Jackson T.; Aryal, Sandeep; Patel, Shaili D.; Cheng, Catherine (Frontiers in Cell and Developmental Biology, 2022)
The transparent ocular lens in the anterior chamber of the eye is responsible for fine focusing of light onto the retina. The lens is entirely cellular with the bulk of the tissue composed of fiber cells, and the anterior hemisphere of the lens is covered by a monolayer of epithelial cells. Lens epithelial cells are important for maintaining fiber cell homeostasis and for continual growth of the lens tissue throughout life. Cataracts, or any opacity in the lens, remain the leading cause of blindness in the world. Following cataract surgery, lens epithelial cells can undergo a process of epithelial-to-mesenchymal transition (EMT) leading to secondary cataracts due to posterior capsular opacification (PCO). Since the epithelial cells make up only a small fraction of the lens, specialized techniques are required to study lens epithelial cell biology and pathology. Studies using native lens epithelial cells often require pooling of samples to obtain enough cells to make sufficient samples for traditional molecular biology techniques. Here, we provide detailed protocols that enable the study of native mouse lens epithelial cells, including immunostaining of the native lens epithelium in flat mounts, extraction of RNA and proteins from pairs of lens epithelial monolayers, and isolation of lens epithelial cells for primary culture. These protocols will enable researchers to gain better insight on representative molecular expression and cellular structure of lens epithelial cells. We also provide comparative data between native, primary culture, and immortalized lens epithelial cells and discuss the advantages and disadvantages of each technique presented.